PKM Pendampingan Digital Marketing untuk Meningkatkan Penjualan UKM Produksi Tahu di Desa Brani Kulon - Cahyuni Novia; Nanda Kurnia Agusmawati; Nurrika Riskya (GUYUB: Journal of Community Engagement, 2022)
Internet-based technology has a great impact on the business world. In addition, technological developments also create great business opportunities. But on the other hand, the increase in internet users is not followed by an increase in the ability of SMEs, especially SMEs to produce tofu by Mrs. Suraye in Brani Kulon Village. The lack of knowledge of the owners of SMEs producing tofu, Mrs. Suraye in Brani Kulon Village, about digital marketing has inspired the community service team to provide assistance and use information and communication technology. Then you can practice it directly by using the Google Maps application and the Tokopedia marketplace. The method used in this service is mentoring and training SME partners in tofu production in using digital marketing for their business. The target to be achieved in this community service is the implementation of digital marketing assistance to increase sales of tofu production SMEs. The result of this service activity is an increase in the knowledge and skills of SME owners in the use of technology, especially the Google Maps application as a means of information on the location of SMEs and the use of Tokopedia accounts as a medium for online sales. The impact of digital marketing is very influential in the expansion of the marketing network so as to increase the sales of MSMEs producing Mrs. Suraye tofu.